JAK2 Mutation-Related Disease and Thrombosis - Vannucchi, Alessandro M.; Guglielmelli, Paola (Seminars in Thrombosis and Hemostasis, 2013)
A recurrent JAK2V617F mutation is typically associated with chronic myeloproliferative neoplasms (MPNs) that include polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis. This mutation results in a gain of function that is credited to underlie most of the pathogenesis and phenotypic characteristics of these disorders; it serves as a key diagnostic marker and represents a suitable target for JAK2 inhibitors. Because cardiovascular events represent the main cause of morbidity and mortality in PV and ET, current patients' risk stratification is based on variables predicting individual thrombotic risk (age and previous thrombotic history). However, evidence is accumulating that supports a role of JAK2V617F mutation as a novel risk factor for thrombosis, although prospective validation has not been provided yet. In this review, we discuss about potential mechanisms that link mutated JAK2 with the thrombotic propensity of MPN and the clinical correlates; hopefully, novel information could result in better patient management.
Keywords: JAK2 mutation; myeloproliferative neoplasms; thrombosis; risk factors; leukocytosis; endothelial cells